Customary Institutions and Religious Moderation in Early Childhood: Mediating Cultural Values through Family Parenting - Sapendi; Rizqina, Aulia Laily; Hayati, Nur (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2026)
Research on religious moderation in early childhood has largely centred on formal educational institutions and families, leaving the role of customary institutions insufficiently examined. This study investigates how customary institutions mediate the transmission of religious moderation values through parenting practices in Pontianak City, West Kalimantan, Indonesia. Using a qualitative design, data were generated through interviews, observation, and document review involving representatives of Malay, Dayak, and Madurese customary institutions, parents of children aged 0 to 8 years, and community figures. The data were analyzed iteratively through coding, categorization, thematic interpretation, and triangulation across data sources. The findings show that customary institutions do not shape children’s religious moderation directly. Instead, they provide cultural narratives, customary philosophies, social norms, and multicultural activities that parents interpret, model, and incorporate into everyday parenting. Children encounter these values through affectionate language, parental guidance, participation in cultural events, and interaction with people from different ethnic and religious backgrounds. The study identifies a mediated pathway linking customary institutions, parental interpretation, and children’s social experience. Cultural authority supported tolerance, empathy, respect, and shared responsibility when institutional programmes remained open to intergroup participation and were reinforced through repeated family involvement. These findings extend discussions of culturally embedded parenting and community-based moral education by positioning customary institutions as intermediary actors between collective traditions and family life. The study also cautions that local culture is not inherently inclusive, since its educational significance depends on how identity is framed and translated within family and community relationships.